Research Review: Epidemiological modelling of attention‐deficit/hyperactivity disorder and conduct disorder for the Global Burden of Disease Study 2010. (4th October 2013) - Erskine, Holly E.; Ferrari, Alize J.; Nelson, Paul; Polanczyk, Guilherme V.; Flaxman, Abraham D.; Vos, Theo; Whiteford, Harvey A.; Scott, James G.
<x xml:space="preserve">Abstract</x> Background The most recent Global Burden of Disease Study (GBD 2010) is the first to include attention‐deficit/hyperactivity disorder (ADHD) and conduct disorder (CD) for burden quantification. We present the epidemiological profiles of ADHD and CD across three time periods for 21 world regions. Methods A systematic review of global epidemiology was conducted for each disorder (based on a literature search of the Medline, PsycInfo and EMBASE databases). A Bayesian metaregression tool was used to derive prevalence estimates by age and sex in three time periods (1990, 2005 and 2010) for 21 world regions including those with little or no data. Prior expert knowledge and covariates were applied to each model to adjust suboptimal data. Final prevalence output for ADHD were adjusted to reflect an equivalent value if studies had measured point prevalence using multiple informants while final prevalence output for CD were adjusted to reflect a value equivalent to CD only. Results Prevalence was pooled for males and females aged 5–19 years with no difference found in global prevalence between the three time periods. Male prevalence of ADHD in 2010 was 2.2% (2.0–2.3) while female prevalence was 0.7% (0.6–0.7). Male prevalence of CD in 2010 was 3.6% (3.3–4.0) while female prevalence was 1.5% (1.4–1.7). ADHD and CD were estimated to be present worldwide with ADHD prevalence showing some regional variation while CD prevalence remained relatively consistent worldwide. Conclusions We present the first prevalence estimates of both ADHD and CD globally and for all world regions. Data were sparse with large parts of the world having no estimates of either disorder. Epidemiological studies are urgently needed in certain parts of the world. Our findings directly informed burden quantification for GBD 2010. As mental disorders gained increased recognition after the first GBD study in 1990, the inclusion of ADHD and CD in GBD 2010 ensures their importance will be recognized alongside other childhood disorders.